Intrinsic Contribution of Perforin to NK-Cell Homeostasis during Mouse Cytomegalovirus Infection - Arapović, Maja; Brizić, Ilija; Popović, Branka; Jurković, Slaven; Jordan, Stefan; Krmpotić, Astrid; Arapović, Jurica; Jonjić, Stipan (Frontiers in Immunology, 2016)
In addition to their role as effector cells in virus control, natural killer (NK) cells have an immunoregulatory function in shaping the antiviral T-cell response. This function is further pronounced in perforin-deficient mice that show the enhanced NK-cell proliferation and cytokine secretion upon mouse cytomegalovirus (MCMV) infection. Here we confirmed that stronger activation and maturation of NK cells in perforin-deficient mice correlates with higher MCMV load. To further characterize the immunoregulatory potential of perforin, we compared the response of NK cells that express or do not express perforin using bone-marrow chimeras. Our results demonstrated that the enhanced proliferation and maturation of NK cells in MCMV-infected bone-marrow chimeras is an intrinsic property of perforin-deficient NK cells. Thus, in addition to confirming that NK-cell proliferation is virus load dependent, our data extend this notion demonstrating that perforin plays an intrinsic role as a feedback mechanism in regulation of NK-cell proliferation during viral infections.